Tech stock valuation : - Hirschey, Mark (Academic Press, 2003)
Financial economists and accountants have investigated the link between a firm's market value and its R&D spending, and various factions advocate a variety of positions on the amount and rate of investment, investors' ability to capture returns on that investment, and ways to measure value, investment, and returns.